Next level sales coaching : how to build a sales team that stays, sells, and succeeds - Johnson, Steve, 1962-; Hawk, Matthew (John Wiley & Sons, Inc., 2020)
"Overcome the biggest hurdles in coaching a sales team to peak performance Next Level Sales Coaching offers insights to sales executives, customer service managers, business owners, and other professional managers on strategies to overcome common challenges in building a "best in class" sales team. Sales performance can impact a company's revenue, profits, market share, and employee retention. The question is, how do you positively impact those goals? The answer is simple: sales improve when your team is better trained, coached, and supported. This book will show you how to further strengthen your sales coaching skills and, as a result, better develop your sales team. When you get better, they get better. When a sales team is led the right way, there is an increased probability they will feel better about themselves, their jobs, stay longer, and become a future sales leader in the company. Many books focus on the symptoms of poor sales performance, but they don't tell you how to solve the problems. Next Level Sales Coaching gives you a proven, step-by-step, process and methodology on how to resolve the most common challenges you will face when leading your sales team. The strategies are built on the best practices of over 10,000 sales managers that we have interviewed, researched and observed in action over the last 35 years. This book covers how to connect with, train, coach and inspire your sales team. Ultimately, it will help you to reduce turnover, improve performance, and increase retention of top performers."--